Investigation Of Potential Weathered Ree-Bearing Granitoid Crust From Dinding District Of Western Tin Belt, Peninsular Malaysia - Yaraghi, Ali (2020)
This research interpreted a green and sustainable exploration strategy of ion-adsorption type REE clay potential deposits with minimum or free radioactive issues in some prone districts of western Peninsula Malaysia. An intensive characterizationstudy was conducted on two sets of samples from Dinding district located within the western part of Malaysian tin granite belt. Understanding REEs characterization andgeochemical behaviour among weathered crusts of granitoids as well as their leachability were the main objectives of this study. The study was conducted based on the field and microscopic investigations, XRD, FTIR Spectroscopy, SEM-EDX, XRF, ICP-MS, CEC determination and batch leaching of clay hosted REEs. Petrographical study and geochemical analysis showed granitoids in Lumut (LU) and Telok Murok (TM) sites were ilmenite-series, mainly peraluminous, S-type which were classified into syeno-granite and monzo-granite, respectively with k-feldspar, quartz, plagioclase and mica group as major minerals. Apatite, monazite, zircon, allanite, titanite and ilmenite were accessory minerals in LU site whilst, TM site was indicated by zircon, apatite and allanite. XRD analysis showed the presence of kaolin and smectite rich clay groups, whilst phlogopite was common mica in parent granites. In both sites, depletion of REE+Y (REY) content in horizon A was considerably apparent, whilst REY enriched in horizon B and/or C. The maximum content of REY could be as high as 3500 ppm in horizon B2 and /or C analyzed by ICP-MS. Total REE content (TRE) of the weathered crust is relatively elevated compared to the parent rocks (3 to 7 times), in horizon B and C of both sites. The chondrite normalized diagrams showed a downward tendency of positive to negative Ce anomaly with LREE enrichment in both sites. However, the mass balance of REE mineral components between each horizon in both sites are different. In batch leaching experiments, TRE extraction levels of ~70% ~ 90% for both sites were achieved with relatively lower extraction of 50-80% for HREEs.